Assessment of growth parameters and yield of pea (Pisum sativum) under different irrigation methods - SINGHAL, NEHA; SHARMA, POONAM; SHARDA, RAKESH; SIAG, MUKESH; CUTTING, NIKHIL GLADWIN (The Indian Journal of Agricultural Sciences, 2021)
Field experiment for pea (Pisum sativum L.) (PB-89) crop was conducted during rabi 2016-17 and 2017-18 at Punjab Agricultural University, Ludhiana. The objective of the experiment was to study the impact of different irrigation methods, viz. drip, furrow and flood irrigation on crop growth parameters and yield of the crop. Better growth parameters, viz. plant height, leaf area index, dry weight of root and shoot and the chlorophyll content were recorded under drip irrigation. Plant height and leaf area index had a positive correlation to yield of the crop. Weight of grain was also positively correlated with the grain yield. There was increase in yields in 2017-18. Yield was found significantly higher under drip irrigation treatments.